SURVEI PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN PADA SATUAN PENDIDIKAN SD, SMP, SMA NEGERI SE-KECAMATAN DONGKO KABUPATEN TRENGGALEK - ABRIAN PRATAMA, SAKTI (Jurnal Pendidikan Olahraga dan Kesehatan, 2015)
Abstrak Pelaksanaan Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) di sekolah mempunyai peranan yang penting, selain itu juga dapat menunjang prestasi pada bidang pelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan. Maka pelaksanaan Pendidikan Jasmani, Olahraga, dan Kesehatan harus ditunjang oleh sarana dan prasarana, ketersediaan tenaga pelaksana, hasil kerja kurun satu tahun terakhir dan prestasi dan penghargaan kurun satu tahun terakhir. Untuk merealisasikan hal di atas, tim Asisten Deputi Olahraga Pendidikan (Asdep Ordik) deputi pemberdayaan Pemuda dan Olahraga, Kementrian Pemuda dan Olahraga Republik Indonesia, telah menyediakan perangkat laporan yang disebut Pangkalan Data Pendidikan Jasmani dan Olahraga Indonesia (PDPJOI). Tujuan dari penelitian ini adalah untuk mengetahui kondisi Pelaksanaan PJOK pada SD, SMP dan SMA Negeri se-Kecamatan Dongko Tahun Ajaran 2014/2015. Metode penelitian ini menggunakan jenis penelitian non eksperimen dengan menggunakan desain survei. Dari tiga satuan pendidikan yang di teliti, satuan pendidikan yang mendapatkan nilai lebih bagus adalah satuan pendidikan SMPN, karena mendapatkan ketersediaan sarana  prasarana kategori "C", ketersediaan tenaga pelaksana kategori "A", hasil kerja kurun satu tahun kategori "B", prestasi dan penghargaan kategori "D", dan total keseluruhan mendapatkan kategori B. Kesimpulannya rekapitulasi data dari Pelaksanaan PJOK pada tingkat SD, SMP, SMA Negeri adalah rata-rata Pelaksanaan PJOK pada satuan pendidikan SD Negeri adalah total 589,33 kategori "C" (cukup), pelaksanaan PJOK pada satuan pendidikan rata-rata SMP Negeri total 626,67 kategori "B" (baik), pelaksanaan PJOK pada satuan pendidikan rata-rata SMA Negeri total 589 kategori "C" (cukup). Kata kunci : Pelaksanaan PJOK, SD Negeri, SMP Negeri, SMA Negeri  Abstract The implementation of sport physical and health education in school is not only has the important roles but also can improve the achievement especially in sport physical and health education's lesson. That is why the implementation of sport physical and health education must be supported by good infrastructure, amount stock of implementer of teacher, work result in one last year, achievement and reward in one last year. For realizing those things, Assistant  Deputy   Sport Education Team, enablenss young and sport deputy, Young and Sport Republic Indonesia Ministry. Have been preparing the set of report called as Basic Data Physical Education and Sport Indonesia. The purpose of this research is to know the real condition of implementation of sport physical and health education in all elementary schools District Dongko in period 2014/2015, all state junior high schools District Dongko in period 2014/2015, all state senior high schools in period 2014/2015. Method of investigation use non experiment investigation with use survey design. From third education unit of investigated, education unit of  get good value is junior high school, because get supported by good infrastructure "C" category, amount stock of implementer of teacher "A" category, work resulting one the last year "B" category, achievement and reward in one last year "D" category, and all total get "B" category. The conclusion of the research about the implementation of sport and health education in grade of state elementary school, junior high school, and senior high school are in the following sentence. The average score in education unit of state elementary school total is 589, 33 and it is including in “C” category, in education unit of state junior high school total is 626, 67 and it is including in “B” category, and in education unit of state senior high school total is 589 and it is including in ”C” category. For additional information, “B” category is good and “C” category is not really good (adequate). Keywords: The implementation of PJOK, state elementary school, junior high school, senior high school.